Strategi Pemasaran Pendidikan Melalui Kegiatan Ekstrakulikuler - Ali Mustofa (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2024)
An educational institution's marketing strategy also affects its performance. In the competition to attract new students, education marketing is crucial. Therefore, educational institutions must have an effective approach to this. This research investigates MA Al-Urwatul Wutsqo Jombang's strategy to gain many students through its extracurricular activities. The purpose of this study is to find out the extracurricular activities at MA Al-Urwatul Wutsqo Jombang and how this strategy is applied to market education. The results showed that MA Al-Urwatul Wutsqo Jombang has implemented marketing well, There are seven things used in marketing, namely concerning products, prices, places, people, promotions, processes, Physical Evidence